Evaluating food front-of-pack labelling: a pan-European survey on consumers' attitudes toward food labelling. (March 2014) - Gregori, Dario; Ballali, Simonetta; Vögele, Claus; Gafare, Claudia Elena; Stefanini, Giulia; Widhalm, Kurt
Abstract Nutrition labels on pre-packaged foods have been widely used as a medium to foster healthier eating habits in the general population, to contribute to a reduction in the incidence and prevalence of diet-related conditions. Yet, there is no convincing evidence that food labels are an effective means to achieve the desired effect at population level. Several factors have been suggested to account for this decoupling of efficacy, e.g. difficulties in understanding the information on food-labels. The present article presents the results of a survey on Europeans' understanding of nutritional labels and evaluation on the communication tools for their diffusion. A total of 7550 phone interviews were conducted in 16 European Countries: Austria, Belgium, Denmark, France, Germany, Greece, Italy, the Netherlands, Poland, Portugal, Czech Republic, Slovenia, Spain, Sweden, United Kingdom and Hungary. Consumers were asked about their opinion on nutritional information provided at different levels and their commitment to healthy behaviour.